Bibliometric mapping of research trends in education, physical education, and sports for the disabled - Karakaya, Yunus E.; Dikmen, Melih; Sahin, Aykut (Citta Aperta Edizioni Srl, 2023)
In this study, a relational systematic map of research trends in education, physical education, and sports for disabled people was prepared with the bibliometric mapping method. Scientific data obtained from the Web of Science (WoS) was used in the research. After the search in the WoS database, 423 studies were accessed, and 415 of these were included in the final analysis by applying the exclusion criteria. The VOSviewer (Visualization of Similarities) program was used for the bibliometric analysis. The results of the research demonstrate that the number of studies in the field has increased from the 1980s to the present day. The studies included in the research were published in 50 different countries, in 133 different journals and were carried out by 770 authors working in 409 different universities/institutions. According to the findings, most of the research, the highest number of citations, and the most influential authors were based in the United States of America. The results showed that the most cited author in this field works collaboratively with many national and international researchers. The results of the research may provide practical information for politicians, practitioners, and lecturers to draw their attention to new research trends and opportunities regarding education, physical education and sports for individuals with disabilities.
Keywords: Disability; Education; Physical education; Sports; Bibliometric analysis; Web of Science